Peran Institusi Pendidikan dalam Pengelolaan Obesitas pada Remaja - Zahtamal zahtamal; Tuti Restuastuti; Fifia Chandra; Hamidah Batubara (STIKes Hang Tuah Pekanbaru, 2020)
Obesity concern is a global issue due to the prevalence is increasing in all age groups, including adolescence group. The objective of the study was to reveal the role of educational institutions in assisting the management of obesity in adolescents. A qualitative descriptive study design was adopted, which was conducted at the Department of Education and Culture and three senior high schools (SMA) in Pekanbaru City which was determined by purposive sampling. The research informants were the head of the Pekanbaru city education and culture office, the principal, teachers, and youth (students). The determination of the number of informants is based on the principles of adequacy and representation. Data were collected by means of in-depth interviews, focus group discussions and observations. Data analysis in the form of qualitative analysis, describe the role of educational institutions in helping the management of obesity in adolescents (students). The results showed that the components that support the management of obesity in adolescents include a strong commitment from the education office, the availability of infrastructure and financial support. Some things that are not yet optimal include; there is no written policy (regulations, decrees, circular letters) specifically aimed at helping adolescent obesity treatment in schools, curriculum in subjects does not support students to be physically active nor does it support the provision of balanced nutrition, and there is still a lack of involvement of various parties comprehensively and across sectors. Overall, it is concluded that the role of educational institutions in managing obesity in adolescents has not been optimal.